Structure of Anecdotal Texts by Class X Students of SMK Nu Kaplongan Based on Learning Styles - Dede Indriany Rahmawati; Ida Zulaeha (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Writing anecdotal texts is an important language skill that requires students to organize ideas coherently according to the appropriate text structure. Differences in learning styles may influence how students develop and structure anecdotal texts. Therefore, this study aimed to describe the structure of anecdotal texts written by tenth-grade students of SMK NU Kaplongan based on visual, auditory, and kinesthetic learning styles. This study employed a qualitative descriptive approach. The research subjects consisted of three students selected through purposive sampling, each representing a visual, auditory, and kinesthetic learning style. The data comprised linguistic units from students' anecdotal texts, including words, phrases, sentences, and paragraphs that reflected the text's structure. Data were collected through a learning style questionnaire and documentation, and were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings revealed that all participants incorporated the full structure of anecdotal texts, comprising abstraction, orientation, crisis, reaction, and coda. However, differences were identified in the way the structures were organized. Visual learners tended to produce more systematic and coherent structures; auditory learners demonstrated relatively complete structures despite some inaccuracies in organizing certain elements; and kinesthetic learners presented complete structures but showed less variation in story development. These findings indicate that learning styles influence the characteristics of students' anecdotal text structures.